Billiary Tract Obstruction due to Gallbladder Carcinoma at Prof. Dr. R. D. Kandou General Hospital: Two Case Reports - Michael Tendean; Toar D. B. Mambu; Leonard A. Melatunan (Medical Scope Journal, 2023)
Abstract: Gallbladder cancer is the fifth most common gastrointestinal malignancy with a high mortality rate. Detection of gallbladder carcinoma in early stages can be difficult, despite improvements in ultrasound and CT-Scan imaging. It is possible to cure gallbladder cancer surgically at an early stage. We reported two cases of gall bladder carcinoma, 65-year-old and 52-year-old females, with the chief complaints of abdominal pain in the right upper quadrant (RUQ) and obstructive jaundice in both cases. The abdominal CT-scans showed circumferentially irregular focal thickening of gallbladder wall, and severe intra and extrahepatic cholestasis. Endoscopic preoperative biliary drainage using biliary stent was performed in one case. Open cholecystectomy with in toto common bile duct resection and portal lymphadenectomy followed by roux en-y hepaticojejunostomy reconstruction were performed for both cases. Both patients are still well with no cancer recurrences over two-year follow-up. The symptoms of gall bladder cancer were non-specific, and commonly included RUQ abdominal pain, weight loss, anorexia, nausea or vomiting, jaundice, and pruritus. Imaging with ultrasound and CT-Scan had improved preoperative diagnosis of gallbladder cancer. Outcomes of patient with incidental finding of gallbladder cancer had better prognosis since it provided the patient to be staged and managed appropriately with resection. In conclusion, early detection of gallbladder cancer results in better surgical outcome and less patient morbidity and mortality which shows its importance. Keywords: gallbladder carcinoma; early-stage detection; common bile duct resection